Prognostic Value of Regression Rate of Plasma EBV DNA After Induction Chemotherapy for Stage II-IVA Nasopharyngeal Carcinoma - Peng, Hao; Chen, Bin-bin; Wang, Xiao-hui; Mo, Yun-Xian; Han, Fei (Frontiers in Oncology, 2021)
Background/Objective: We aimed to explore the prognostic value of regression rate (RR) of plasma Epstein-Barr virus (EBV) DNA after induction chemotherapy (IC) in patients with stage II-IVA nasopharyngeal carcinoma (NPC). Methods: Eligible patients receiving IC followed by concurrent chemoradiotherapy were included. The cut-off value of pre-treatment EBV DNA (pre-IC DNA) and RR were identified by receiver operating curve (ROC). Recursive partitioning analysis (RPA) was applied to create new staging. Harrell’s c-index and time-independent ROC were employed to compare different RPA staging. Results: In total, 1184 patients were included. The cut-off values of pre-IC DNA and RR were 16200 copies/ml and 95.127% for patients receiving 2 cycles, and 5520 copies/ml and 99.994% for those receiving 3 cycles. Notably, we only focused on patients receiving 2 cycles of IC. Patients with a RR > 95.127% had a significantly better 5-year overall survival (OS) than those ≤ 95.127% (86.2% vs. 54.3%, P < 0.001). Then, RPA1 (pre-IC DNA + TNM staging + RR) and RPA2 (pre-IC DNA + TNM staging + post-IC EBV DNA [post-IC DNA]) staging systems were created. RPA1 staging achieved stronger power in OS prediction than RPA2 staging and TNM staging (c-index: 0.763 [0.714-0.812] vs. 0.735 [0.684-0.786] vs. 0.677 [0.604-0.749]; AUC: 0.736 vs. 0.714 vs. 0.628), indicating that RR had stronger prognostic power than post-IC DNA. Moreover, patients with stage III-IVRPA1 could benefit from high concurrent cumulative platinum dose (≥ 160mg/m2). Conclusion: RR in conjunction with current TNM staging could better conducted risk stratification, prognosis prediction and help to guide precise concurrent chemotherapy.